2020
DOI: 10.1002/lpor.202070069
|View full text |Cite
|
Sign up to set email alerts
|

Exciton‐Exciton Annihilation Dynamics: Excitonic Transport and Intervalley Scattering Dynamics in Large‐Size Exfoliated MoSe2 Monolayer Investigated by Heterodyned Transient Grating Spectroscopy (Laser Photonics Rev. 14(12)/2020)

Abstract: Exciton intervalley scattering, annihilation, relaxation dynamics, and diffusive transport in monolayer transition metal dichalcogenides (TMDCs) are central to the functionality of devices based on them. In article number 2000029 by Jingyi Zhu, Paul H. M. van Loosdrecht, and co‐workers investigate exciton‐exciton annihilation dynamics and its effect in the distortion of the diffusion grating in an exfoliated monolayer TMDC, MoSe2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[61,144,173] At higher generation rates, the PL QY of MoS 2 (and other TMDCs) drops as recombination at high exciton densities is dominated by the annihilation of two adjacent excitons, a process so-called exciton-exciton annihilation (EEA). [99,[217][218][219][220] EEA is a process in which neutral excitons recombine nonradiatively in the course of colliding with other excitons, causing a reduction in the luminescent efficiency of the material at higher generation rates. [99,[217][218][219][220] To eliminate the efficiency droop in 2D semiconductors, a detailed investigation on the origin of the EEA process is required.…”
Section: Elimination Of Efficiency Droopmentioning
confidence: 99%
See 1 more Smart Citation
“…[61,144,173] At higher generation rates, the PL QY of MoS 2 (and other TMDCs) drops as recombination at high exciton densities is dominated by the annihilation of two adjacent excitons, a process so-called exciton-exciton annihilation (EEA). [99,[217][218][219][220] EEA is a process in which neutral excitons recombine nonradiatively in the course of colliding with other excitons, causing a reduction in the luminescent efficiency of the material at higher generation rates. [99,[217][218][219][220] To eliminate the efficiency droop in 2D semiconductors, a detailed investigation on the origin of the EEA process is required.…”
Section: Elimination Of Efficiency Droopmentioning
confidence: 99%
“…[99,[217][218][219][220] EEA is a process in which neutral excitons recombine nonradiatively in the course of colliding with other excitons, causing a reduction in the luminescent efficiency of the material at higher generation rates. [99,[217][218][219][220] To eliminate the efficiency droop in 2D semiconductors, a detailed investigation on the origin of the EEA process is required. It is found that the lifetime of excitons is inversely related to the EEA coefficient (C EAA ), a parameter that measures the rate of annihilation.…”
Section: Elimination Of Efficiency Droopmentioning
confidence: 99%
“…Transient grating based approaches have been extensively used for the measurement of the diffusion properties of charge carriers. Among the successful examples are applications to studying exciton diffusion [ 16 ] and, more recently, 2D materials such as WSe 2 [ 25 ] and MoSe 2 [ 26 ] monolayers. Another example are ambipolar mobilities, e.g., the combined electron and hole mobility, in semiconductors [ 27–29 ] including the recent observation of high ambipolar mobility and ultra‐high thermal conductivity in cubic boron arsenide [ 30 ] by the Chen group, a finding that was in parallel reported by Yue et al., using widefield imaging‐based transient reflection SPTM: [ 31 ] This is a great example of how compatible information can be obtained using different SPTM techniques.…”
Section: Particle Transport Studied Using Sptmmentioning
confidence: 99%
“…More recently, the same approach was used to study rapid valley depolarization in 2D materials, occurring within 170 femtoseconds for MoSe 2 . [ 26,34 ]…”
Section: Particle Transport Studied Using Sptmmentioning
confidence: 99%